2013
DOI: 10.11622/smedj.2013112
|View full text |Cite
|
Sign up to set email alerts
|

Ministry of Health Clinical Practice Guidelines: Dementia

Abstract: The Ministry of Health (MOH) has updated the clinical practice guidelines on Dementia to provide doctors and patients in Singapore with evidence-based treatment for dementia. This article reproduces the introduction and executive summary (with recommendations from the guidelines) from the MOH clinical practice guidelines on Dementia, for the information of readers of the Singapore Medical Journal. Chapters and page numbers mentioned in the reproduced extract refer to the full text of the guidelines, which are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Three pointed out that RCT evidence of the long-term benefits of ChEI therapy, particularly among those with severe disease, was limited. (22, 30, 32) Another (25) suggested that the evidence was insufficient to determine the optimal duration of therapy, but that initial benefits (either improvement or stabilization) should be expected within three months. Two (23, 33) warned against exclusively relying on MMSE score and recommended considering functional and behavioral assessment, in conjunction with the family/caregiver assessment of the patient’s condition.…”
Section: Resultsmentioning
confidence: 99%
“…Three pointed out that RCT evidence of the long-term benefits of ChEI therapy, particularly among those with severe disease, was limited. (22, 30, 32) Another (25) suggested that the evidence was insufficient to determine the optimal duration of therapy, but that initial benefits (either improvement or stabilization) should be expected within three months. Two (23, 33) warned against exclusively relying on MMSE score and recommended considering functional and behavioral assessment, in conjunction with the family/caregiver assessment of the patient’s condition.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the participants might not be representative of the entire target population at risk of cognitive impairment (older persons aged≥65 years) [26], since recruitment was carried out only at one location with multiple exclusion criteria. Furthermore, the study population was classified solely on the basis of the MoCA scores, which is a screening tool and not considered diagnostic of cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based clinical guidelines for dementia care recommend a holistic approach to ameliorate disease progression and improve QOL of PWD [4, 5]. These include interdisciplinary case management targeting PWDs and their caregivers, community-based and home-based services, and psychoeducational and care transition programmes [6].…”
Section: Introductionmentioning
confidence: 99%